Hierarchical Trade and Endogenous Price Distortions - Hans Gersbach; Hans Haller (ETH Zurich, CER-ETH - Center of Economic Research, 2007)
We study the allocation of commodities through a two-stage hierarchy of competitive markets. Groups or countries trade at global prices while individuals within a group trade at local prices. We identify the free trade and the autarky equilibrium as polar cases. We show that no other two-stage market equilibria exist if the commodity space is two-dimensional. An example demonstrates that other, so-called intermediate equilibria exist for three-dimensional commodity spaces. The example also exhibits endogenous price distortions in third countries when some countries follow distortionary trade policies. We give two existence proofs for intermediate equilibria in higher dimensions. Each proof provides an explicit construction of special classes of intermediate equilibria.
Keywords: 330